Amount of DNA in plasma and cancer risk: A prospective study - Gormally, E; Hainaut, P; Caboux, E; Airoldi, L; Autrup, H; Malaveille, C; Dunning, A; Garte, S; Matullo, G; Overvad, K; Tjonneland, A; Clavel-Chapelon, F; et al. (2004)
Levels of plasma DNA concentrations in cancer patients have been shown to be higher than the plasma DNA concentrations found in healthy subjects. The value of plasma DNA levels for development of neoplastic or pulmonary disease was evaluated in a large prospective study. Plasma samples (n = I,184) were analyzed from 776 controls, 359 cases of cancer (lung, bladder, oral cavity, pharynx, larynx, leukemia) and 49 deaths from chronic obstructive pulmonary disease (COPD), including never smokers and ex-smokers, from 9 countries across Europe. The amount of plasma DNA was variable across the European Prospective Investigation into Cancer and Nutrition (EPIC) centers. High DNA concentrations in some centers might be due to the type of population recruited and/or the treatment of the samples. An elevated and statistically significant odds ratio (OR) was found for COPD deaths (OR = 2.53; 95% CI = 1.06-6.02), while nonsignificant increased ORs were present for oral cancers, cancers of the pharynx and larynx and leukemia. When the analyses were stratified by time since recruitment (below or above 36 months), the increased ORs were limited to the more recent period of recruitment, i.e., a time elapsed between blood drawing and disease onset lower than 36 months. This was particularly true for COPD deaths (OR = 12.7; 95% CI = 1.57-103) and leukemia (OR = 2.37; 95% CI = 1.20-4.67). © 2004 Wiley-Liss, Inc.